FINANCIAL MANAGEMENT TOOLS OF THE RESEARCH PROJECTS AT A HIGHER EDUCATION INSTITUTION - Kazarinova, N.L. (Perm Federal Research Centre Journal, 2016)
The article discusses the financial management tools for research activities of higher school taking into account different sources of funding. The approaches to planning, monitoring, effectiveness of the use of finance providing research are offered